JQuery mobile web development essentials : build a powerful and practical jQuery-based framework in order to create mobile-optimized websites /: build a powerful and practical jQuery-based framework in order to create mobile-optimized websites. (2016) - Camden, Raymond; Matthews, Andy
No abstract available